Mathematical simulation of the phototransistors - Anilionienė, Julija (Lietuvos matematikos rinkinys, 2023)
There are presented the model of the phototransistors and evaluated their non-linearity‘s. For simulation non-linearity‘s influence in a signal distortion the functional Voltera series are developed.
Keywords: phototransistor; optical fiber; photo receiver